Teachers’ Information and Communication Technology (ICT) Skills Assessment: Basis for a Comprehensive ICT Training Program - Bayucca, Shallimar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The study described the extent of knowledge in ICT skills of 180 teachers as a basis for a training plan in a selected schools division in Region 3. A descriptive survey method was utilized having a weighted mean and standard deviation to treat the data collected. It was concluded that the teachers displayed a proficient extent of knowledge in basic ICT skills. However, some of the skills enumerated have a low mean and were close to the adjacent group scale of the lower level of knowledge. Furthermore, they showed limited knowledge in some advanced computer applications which are necessary for the construction of instructional materials. The self-assessment revealed that they are knowledgeable in ICT skills, but they do not know how to use it in complex applications. The skills for development based on the training needs assessment reiterated a combination of skills which further clarified that not all skills under a certain application are known. It is then recommended that training needs assessment should always be conducted by school administrators to gather data on the actual needs of the teachers as a basis in planning a thorough training matrix to ensure that the development and training provided are based on the needs of the teachers.